2014
DOI: 10.1016/j.apmr.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Instrumenting the Balance Error Scoring System for Use With Patients Reporting Persistent Balance Problems After Mild Traumatic Brain Injury

Abstract: A concussion may disrupt the sensory processing required for optimal postural control, which was measured by sway during quiet stance. These results suggest that the use of portable inertial sensors may be useful in the move toward more objective and sensitive measures of balance control postconcussion, but more work is needed to increase sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 30 publications
(31 reference statements)
4
116
0
Order By: Relevance
“…41 In an effort to improve concussion detection with the mBESS, King et al 24 added instrumentation in the form of an inertial sensor (accelerometer and gyroscope). The instrumented mBESS was found to be significantly better at detecting concussion (AUC = 0.81, 95% CI 0.64-0.990) than the noninstrumented mBESS (AUC = 0.64, 95% CI 0.42-0.86).…”
Section: Detecting Concussionmentioning
confidence: 99%
“…41 In an effort to improve concussion detection with the mBESS, King et al 24 added instrumentation in the form of an inertial sensor (accelerometer and gyroscope). The instrumented mBESS was found to be significantly better at detecting concussion (AUC = 0.81, 95% CI 0.64-0.990) than the noninstrumented mBESS (AUC = 0.64, 95% CI 0.42-0.86).…”
Section: Detecting Concussionmentioning
confidence: 99%
“…The Multiple Errands Test (MET; Shallice & Burgess, 1991) is an example of a multitask assessment of executive functioning based on five demands of multitasking: (1) performing multiple but discrete tasks that vary in priority, complexity, and length; (2) managing interleaving and dovetailing tasks; (3) performing tasks without feedback; (4) dealing with interruptions, reprioritization, and rule changes; and (5) self-initiating task changes within the activity (Burgess, 2000). The many versions of the MET involve completing at least 10 unrelated tasks while complying with a series of rules in either a shopping mall or hospital lobby setting (Alderman, Burgess, Knight, & Henman, 2003;CuberosUrbano et al, 2013;Dawson et al, 2009;Morrison et al, 2013). Although the MET appears to assess "the central aspects of executive functioning in everyday life" (Frisch et al, 2012, p. 257), it has yet to be widely adopted in clinical practice because of site-specific validation requirements, time-intensive administration, and a lack of standardized scoring manuals specific to each site (Radomski & Morrison, 2014).…”
Section: Objectivesmentioning
confidence: 99%
“…Early work investigating the use of IMUs in balance assessment has shown that a static balance assessment, instrumented with an IMU mounted on the lumbar spine, was not as effective as the traditional subjectively scored assessment in identifying balance deficits post-concussion (Furman et al, 2013). More recently, King et al (2014) demonstrated improved levels of sensitivity and specificity from the instrumented balance error scoring system (BESS). It is likely that the conflicting results are due to the different quantified variables selected in the two studies.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems address some of the aforementioned limitations of traditional motion capture, as they allow for inexpensive, accessible quantification of human movement, in an unconstrained environment (Giggins et al, 2013). These IMU systems have been used in the objective quantification of a range of activities, from static balance tasks (King et al, 2014, Alberts et al, 2015, Furman et al, 2013, to dynamic tasks such as the squat and single leg squat , walking (Zijlstra andHof, 2003, Yang et al, 2013) and running (Lee et al, 2010). Early work investigating the use of IMUs in balance assessment has shown that a static balance assessment, instrumented with an IMU mounted on the lumbar spine, was not as effective as the traditional subjectively scored assessment in identifying balance deficits post-concussion (Furman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation